Konsep Uban dalam Tafsir Al-Munir - Hidayat, Muhammad Taufiq; Sandi, Tri; Zein, Achyar; Astuti, Rahayu Fuji (IAI Nasional Laa Roiba Bogor, 2024)
This research was conducted to find out what is meant by gray hair and what is the concept of gray hair in Tafsir Al-Munir, gray hair comes from the words شَابَ - يَشِيْبُ - شَيْب, which means white hair on the top of the head, either a little or a lot. The plural form of the word شَيْب is شيُوْب. The word شَيْب in the Koran is found in three suras, including surah Maryam [19] verse 4 with the pronunciation شَيْبا surah al-Rûm [30] verse 54 with the pronunciation شَيْبةَ, and surah al-Muzzammil [73] verse 17 with the pronunciation شِيْب ا. Gray hair is hair that is white or starting to turn white. Gray hair is described in the Koran as a biological signal indicating that a person is old, as well as a theological signal that a person will soon be returned to his Lord. This research examines what is meant by gray hair and the concept of gray hair in Al Munir's interpretation. This research uses qualitative research methods and library research. From the results of this research, it can be concluded that the concept of gray hair in Wahba Al-Zuhaili's Tafsir Al-Munir is a reminder for those of us who will have gray hair to introspect ourselves about the message of its growth and implies obedience, even for every gray hair that grows in between. Between our hair there is a pile of wise advice to equip us to follow the path of life, to strengthen our beliefs, give birth to wisdom, make the sad happy, dispel despair, and give birth to a million hopes.